(untitled) (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 1997)
The existence of a Poisson structure on the phase space of mechanical systems with a fixed constraint satisfying the geometrical property that any conservative mechanical system with this constraint is itself hamiltonian (with respect to the Poisson structure) implies the integrability of the constraint. Two others equivalent geometrical properties are also presented.